Pengaruh Variasi Serat Rami, Limbah Rami, dan Rami Kerok sebagai Penguat Terhadap Kekuatan Tarik Papan Komposit Polipropilena Daur Ulang - Primananda, Ade; Sabila, Faroh; Rebia, Rina Afiani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The purpose of this study was to evaluate the mechanical properties of composites made from recycled polypropylene reinforced with natural ramie fiber (SR), ramie waste fiber (LR), and scraped ramie fiber (RK). Recycled polypropylene was used as the binder material, while ramie fiber (SR), ramie waste fiber (LR), and scraped ramie fiber (RK) were processed by alkalization to improve the adhesion between the layers. Composite fabrication was performed by varying the ratio between matrix and reinforcer A (70/30), B (60/40), and C (50/50) using a hot press machine. Tensile test was performed according to ASTM D-638 standard. The test results showed that the composite reinforced with scraped ramie fibers (RK) produced a maximum stress of 9.26 MPa at the A3 (70/30) ratio, and the highest strain reached 7.6% at the B3 (60/40) and C3 (50/30) ratios. The more uniform structure of scraped ramie fibers (RK) was shown to contribute to a better stress distribution compared to ramie fibers (SR) and ramie waste (LR). Thus, scraped ramie fibers (RK) can be identified as the most optimal reinforcing material for recycled polypropylene composites.